Two-stage gradient-pore microporous layers for enhanced energy production and durability in PEM fuel cells - Saad S. Alrwashdeh (International Journal of Renewable Energy Development, 2026)
Coupled mass, heat, and water transport in proton exchange membrane fuel cells (PEMFCs) critically depend on the microporous layer (MPL), but traditional uniform-pore MPLs are restricted by inherent trade-offs between the accessibility of reactants and the removal of liquid-water. This work presents a two-stage gradient-pore MPL structure and demonstrates its efficiency in terms of a fully coupled, non-isothermal Multiphysics modelling framework, the solution presented is theory-based and mitigates the classical trade-off between gas transport and liquid-water management by introducing a staged pore/porosity architecture that improves oxygen accessibility while promoting directional water evacuation. The proposed design uses a step-pore-size and porosity distribution throughout the MPL thickness to apply a directional capillary pressure gradient so that selective evacuation of water can occur to maintain catalyst-layer hydration. The optimized design is 12 to 18% more peak power density, 10 to 15% higher cell voltage (high current densities 1.5 A.cm-1 and higher), and 30% less cathode liquid saturation than a conventional MPL operating under the same conditions. Thermal analysis also shows that there was 25-35% decrease in temperature non-uniformity, which shows better homogeneity in current density and means that the hotspots causing degradation were caused to fail. Operating-regime mapping validates a strong transition between a transport-limited and optimal performance space, exhibiting increased robustness over a broad operating span. Such findings make pore-gradient engineering a physically based and scalable optimization strategy of improving energy production, thermal stability and durability of next-generation PEM fuel cells concurrently.